A Nazi Past : Recasting German Identity in Postwar Europe - Paehler, Katrin; Messenger, David A. (Book collections on Project MUSE., 2015)
Since the end of World War II, historians and psychologists have investigated the factors that motivated Germans to become Nazis before and during the war. While most studies have focused on the high-level figures who were tried at Nuremberg, much less is known about the hundreds of SS members, party functionaries, and intelligence agents who quietly navigated the transition to postwar life and successfully assimilated into a changed society after the war ended. In A Nazi Past, German and American scholars examine the lives and careers of men like Hans Globke -- who not only escaped punishment for his prominent involvement in formulating the Third Reich's anti-Semitic legislation, but also forged a successful new political career. They also consider the story of Gestapo employee Gertrud Slottke, who exhibited high productivity and ambition in sending Dutch Jews to Auschwitz but eluded trial for fifteen years. Additionally, the contributors explore how a network of Nazi spies and diplomats who recast their identities in Franco's Spain, far from the denazification proceedings in Germany. Previous studies have emphasized how former Nazis hid or downplayed their wartime affiliations and actions as they struggled to invent a new life for themselves after 1945, but this fascinating work shows that many of these individuals actively used their pasts to recast themselves in a democratic, Cold War setting. Based on extensive archival research as well as recently declassified US intelligence, A Nazi Past contributes greatly to our understanding of the postwar politics of memory.